Macrofungi diversity in secondary forest of three forest trails - Pit, Norshipha (2018)
Lowland tropical forests consist of different types of forest trails that include diverse plants, animals and fungi. We examined whether macrofungi diversity of forest trail was associated with length of forest trail, disturbance, sizes and microclimate in three urban forest in Selangor, Malaysia. Macrofungi were collected along the trails with 1.5km length and 30 transect were opened and environmental parameters; soil moisture, soil pH, temperature, relative humidity and wind speed. In total, 254 macro fungi were collected along the trails in forest sites. The species richness and abundance of macrofungi the sites were affected by the size of the baseline and forest patches. Meanwhile, Sungai Lalang Forest Reserve recorded the highest species richness and abundance of macrofungi, followed by Bukit Cerakah Forest Reserve and Ayer Hitam Forest Reserve had the lowest in number of individuals and species.